Knowledge Services Management Organizing Around Internal Markets - Mills, Peter K.; Snyder, Kevin M.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
This book examines the transformation of the traditional workplace and responds to the demand for fresh approaches to the challenges faced by managers in designing knowledge services. Rapid technological development and changing economic conditions have asserted significant influence on the work landscape for both workers and management; most notably, that the means of production are controlled by workers themselves. The response is a growing awareness that the work landscape for knowledge services can no longer be effectively managed by relying on the traditional hierarchical paradigm. Given these current challenges, the design framework presented in this book is based on internal market principles along with customer integration into the boundaries of the organization. This framework initiates new and effective ways of designing knowledge services for sustained competitive advantage. The indispensable role of customer/client in the operations of these organizations is examined, as is the creation of the "Proventure Workplace", a work environment which accentuates jobs requiring rich cognitive skills for continuing innovation and creativity. By adopting an internal market perspective the firm can integrate the science and art of management with the design realities of contemporary knowledge services. Knowledge Services Management provides valuable tools for readers involved in all aspects of knowledge services from researchers to managers and students alike.
Defining Competitive Advantage in Knowledge Services -- Understanding The Logic Of Knowledge Service Sustainability: Customer Alliances -- Building Advantage: Managing Customer Alliances By Professional Distance -- Building Knowledge Advantage: Internal Market Imperatives -- Building Advantage: Management By Mistrust In Controlling Empowered Proventure Workers -- Building Advantage: Designing The Right Structure For Knowledge Services -- The Internal Promotion Of Ideas -- Conclusion.
Keywords: Business; Management science; Leadership; Organization; Planning; Management information systems; Computer science; Business and Management; Business Strategy/Leadership.; Management of Computing and Information Systems; Business and Management, general; Organization; Electronic books